Retrospective Comparison of Ultrasound and Magnetic Resonance Imaging as Diagnostic Tools in Pregnant Women with Abnormal Placentation - Ahmed Mousa (Pakistan Journal of Medical & Health Sciences, 2022)
Postpartum hemorrhage is the leading cause of maternal death worldwide, and Placenta Accreta (PA) is a major contributor. Although advancements in obstetric practices have led to a decline in maternal mortality, PA remains challenging to diagnose and manage. Current diagnostic tools include ultrasound (U/S) and Magnetic Resonance Imaging (MRI); however, the sensitivity and specificity of these techniques in diagnosing Placenta Accreta Spectrum (PAS) are widely debated. Objective: To compare the accuracy of U/S and MRI in the diagnosis of PAS. Methods: A retrospective analysis of pregnant women in their second and third trimesters suspected to have PAS was conducted. Women with both antenatal U/S and MRI who delivered in Dr. Soliman Fakeeh Hospital between 1st October 2014 and 2nd February 2019 were included. Results: Of the 46 women included in the study, MRI corrected the diagnosis of 13 patients (28%) and confirmed the U/S diagnosis of 19 patients (41%). However, MRI also resulted in an incorrect change in diagnosis of eight patients (17%), and an incorrect confirmation of U/S diagnosis of six patients (13%). Statistical analyses of both U/S and MRI in the diagnosis of PAS showed that U/S sensitivity and specificity were 40% and 75%, respectively, whereas MRI sensitivity and specificity were 86% and 58%, respectively. Conclusion: MRI was more sensitive than U/S in identifying placental invasion into the uterine wall. Therefore, we recommend MRI examination for all patients suspected to have PAS.